An Unbalanced Battle in Excellence: Revealing Effect of Ni/Co Occupancy on Water Splitting and Oxygen Reduction Reactions in Triple‐Conducting Oxides for Protonic Ceramic Electrochemical Cells. Issue 30 (29th June 2022) - Tang, Wei; Ding, Hanping; Bian, Wenjuan; Regalado Vera, Clarita Y.; Gomez, Joshua Y.; Dong, Yanhao; Li, Ju; Wu, Wei; Fan, WeiWei; Zhou, Meng; Gore, Colin; Blackburn, Bryan M.; et al.
Abstract: Porous electrodes that conduct electrons, protons, and oxygen ions with dramatically expanded catalytic active sites can replace conventional electrodes with sluggish kinetics in protonic ceramic electrochemical cells. In this work, a strategy is utilized to promote triple conduction by facilitating proton conduction in praseodymium cobaltite perovskite through engineering non‐equivalent B‐site Ni/Co occupancy. Surface infrared spectroscopy is used to study the dehydration behavior, which proves the existence of protons in the perovskite lattice. The proton mobility and proton stability are investigated by hydrogen/deuterium (H/D) isotope exchange and temperature‐programmed desorption. It is observed that the increased nickel replacement on the B‐site has a positive impact on proton defect stability, catalytic activity, and electrochemical performance. This doping strategy is demonstrated to be a promising pathway to increase catalytic activity toward the oxygen reduction and water splitting reactions. The chosen PrNi0.7 Co0.3 O3− δ oxygen electrode demonstrates excellent full‐cell performance with high electrolysis current density of −1.48 A cm −2 at 1.3 V and a peak fuel‐cell power density of 0.95 W cm −2 at 600 °C and also enables lower‐temperature operations down to 350 °C, and superior long‐term durability. Abstract : Triple‐conducting perovskite PrNi0.7 Co0.3 O3 −δ is developed and optimized as a new oxygen electrode in the protonic ceramic electrochemical cell, which shows superior fuel cell and electrolysis performances and can be operated at a low temperature (350 °C). The proton behavior of hydration/dehydration and hydrogen/deuterium isotope exchange is comprehensively studied to prove the proton existence and movement.